2023
DOI: 10.1002/ctm2.1443
|View full text |Cite
|
Sign up to set email alerts
|

Cullin‐associated and neddylation‐dissociated 1 regulate reprogramming of lipid metabolism through SKP1‐Cullin‐1‐F‐boxFBXO11‐mediated heterogeneous nuclear ribonucleoprotein A2/B1 ubiquitination and promote hepatocellular carcinoma

Hao Zhang,
Peng Xia,
Zhangshuo Yang
et al.

Abstract: BackgroundEnhanced de novo lipogenesis is essential for hepatocellular carcinoma (HCC). Abnormally high cullin‐associated and neddylation‐dissociated 1 (CAND1) expression is associated with poor clinical prognosis in HCC. The SKP1‐Cullin‐1‐F‐box (SCF) complex consists of the SKP1, Cullin‐1 and F‐box proteins (FBPs) and performs multiple functions including adipogenesis. SCF complex was modulated by CAND1, but Whether and how the CAND1 promotes HCC by regulating SCF complex and lipogenesis are unknown.MethodsHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In addition to glucose metabolism, the post-translation modifications of hnRNPs exert other aspects on cellular metabolism. The ubiquitination of PTBP1 and hnRNPA2/B1 affect lipogenesis in intrahepatic cholangiocarcinoma [87] and hepatocellular carcinoma [88]. Additionally, hnRNPK phosphorylation influences mRNA metabolism [89].…”
Section: Epigenetic Modifications Of Hnrnps Affect Glycolysis Of Tumo...mentioning
confidence: 99%
“…In addition to glucose metabolism, the post-translation modifications of hnRNPs exert other aspects on cellular metabolism. The ubiquitination of PTBP1 and hnRNPA2/B1 affect lipogenesis in intrahepatic cholangiocarcinoma [87] and hepatocellular carcinoma [88]. Additionally, hnRNPK phosphorylation influences mRNA metabolism [89].…”
Section: Epigenetic Modifications Of Hnrnps Affect Glycolysis Of Tumo...mentioning
confidence: 99%
“…Consequently, CAND1 has been identified as an oncogene of HCC. [ 85 ] The NAD(P)H quinone oxidoreductase-1/p53 target SREBP1 forms a signaling axis to enhance the content of lipids, including TAG and cholesterol, and maintain Snail protein levels by restraining its ubiquitylation, thus mediating the EMT, angiogenesis, and proliferation while inhibiting autophagy in HCC, which makes it a potential prognostic biomarker. [ 86 ] Liu et al [ 87 ] reported that stomatin-like protein 2 (SLP2) could be a prospective prognostic biomarker for HCC.…”
Section: Lipid Metabolic Reprogramming In Hccmentioning
confidence: 99%
“…Zuo et al [ 104 ] developed a new-type nanoplatform based on polymeric nanoparticles and poly (lactic/glycolic) acid, encapsulating si-LINC00958 and spermidine, which can remarkably suppress the growth and prolong the overall survival of HCC model mice without prominent hepatotoxicity and nephrotoxicity. Zhang et al [ 85 ] utilized the adeno-associated virus injections to knockdown CAND1, downregulating the expression of downstream genes, including FASN, ACC1, and ACLY. This had a restraining effect on HCC growth by reducing the accumulation of lipids, which demonstrates that regulation of the CAND1-SCFFBXO11-hnRNPA2B1 axis may be a potential therapeutic target.…”
Section: Lipid Metabolism As Therapeutic Targetsmentioning
confidence: 99%
“…Nowadays, many scholars have applied URGs related characteristics to forecast the future course and immune reaction of various types of cancer, such as lung adenocarcinoma and endometrial cancer, the prognostic signature based on URGs performed well in predicting the infiltration of immune cells and the level of tumor mutation burden (TMB) within the TME and the effectiveness of immunotherapy for cancer treatment [ 13 , 14 ]. There were several studies have uncovered the relationship of URGs and the initiation and development of HCC, nevertheless, the role of URGs in HCC has not been systematically analyzed [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%